2014
DOI: 10.1136/sextrans-2014-051589
|View full text |Cite
|
Sign up to set email alerts
|

Syphilis infection, sexual practices and bisexual behaviour among men who have sex with men and transgender women: a cross-sectional study

Abstract: The prevalence of syphilis infection and risk sexual behaviour were high in the two samples, especially among TW. High levels of bisexual behaviours and low rates of consistent condom use indicate potential HIV/STIs transmission into the heterosexual population. This finding indicates the need and urgency for implementing more effective integrated programmes targeting MSM/TW for the prevention of syphilis and other STIs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
23
1
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 25 publications
(22 reference statements)
2
23
1
3
Order By: Relevance
“…The prevalence of suspected STD infections (24.4%) found in our study was much higher than reported among MSM in Guangzhou (23.2% in 2012 and 17.0% in 2013) [25] and central Brazil (4.3%) [26], but lower than among MSM in the Jiangsu province of China (34.1%) [27] and El Salvador (49.8%) [28] and among female sex workers (FSWs) in Shanxi province (53.6%) [29] of China (the comparisons of prevalence of suspected STD infection were all made under the same definition). The HIV prevalence among suspected STD-infected MSM was 16.7%, which was also higher than Chinese MSM in general (6.5%) [30] and Chinese FSWs (0.2%) [31], as reported in two recently published meta-analyses.…”
Section: Discussioncontrasting
confidence: 63%
“…The prevalence of suspected STD infections (24.4%) found in our study was much higher than reported among MSM in Guangzhou (23.2% in 2012 and 17.0% in 2013) [25] and central Brazil (4.3%) [26], but lower than among MSM in the Jiangsu province of China (34.1%) [27] and El Salvador (49.8%) [28] and among female sex workers (FSWs) in Shanxi province (53.6%) [29] of China (the comparisons of prevalence of suspected STD infection were all made under the same definition). The HIV prevalence among suspected STD-infected MSM was 16.7%, which was also higher than Chinese MSM in general (6.5%) [30] and Chinese FSWs (0.2%) [31], as reported in two recently published meta-analyses.…”
Section: Discussioncontrasting
confidence: 63%
“…Syphilis is a systemic disease caused by the spirochaete Treponema pallidum and is one of the oldest and most well-known diseases, for which curative treatment is available and efficient. Several studies have recently reported its resurgence, particularly in specific populations, especially in communities of men who have sex with men (MSM) in many parts of the world 6-8,12,23 .…”
Section: Introductionmentioning
confidence: 99%
“…2,4 Despite the existence of inexpensive and effective antimicrobial therapy, syphilis has increased significantly in vulnerable groups, including men who have sex with men (MSM), transgender women (TW), commercial sex workers (CSWs), and prisoners. [5][6][7][8] Prison populations are considered to be at high risk for STIs, including syphilis, due to risk behaviors such as intravenous drug use, homosexual contact with unprotected sexual practices, and multiple sexual partners. 8,9 Although syphilis control strategies are well established, some studies have shown significantly increasing rates of T. pallidum infection among prisoners.…”
Section: Introductionmentioning
confidence: 99%